American big business in Britain and Germany : a comparative history of two "special relationships" in the 20th century - Berghahn, Volker R. (Volker Rolf), 1938- (UPCC book collections on Project MUSE. History Supplement., 2014)
"While America's relationship with Britain has often been deemed unique, especially during the two world wars when Germany was a common enemy, the American business sector actually had a greater affinity with Germany for most of the twentieth century. American Big Business in Britain and Germany examines the triangular relationship between the American, British, and German business communities and how the special relationship that Britain believed it had with the United States was supplanted by one between America and Germany. Volker Berghahn begins with the pre-1914 period and moves through the 1920s, when American investments supported German reconstruction rather than British industry. The Nazi seizure of power in 1933 led to a reversal in German-American relations, forcing American corporations to consider cutting their losses or collaborating with a regime that was inexorably moving toward war. Although Britain hoped that the wartime economic alliance with the United States would continue after World War II, the American business community reconnected with West Germany to rebuild Europe's economy. And while Britain thought they had established their special relationship with America once again in the 1980s and 90s, in actuality it was the Germans who, with American help, had acquired an informal economic empire on the European continent. American Big Business in Britain and Germany uncovers the surprising and differing relationships of the American business community with two major European trading partners from 1900 through the twentieth century"--Provided by publisher.